An Independent Validation of 2010 Tumor-Node-Metastasis Classification for Renal Cell Carcinoma: A Multi-center Study by the Urooncology Association of Turkey Renal Cancer-Study Group - (:unkn) unknown (GALENOS YAYINCILIK, 2017)
Objective: The American Joint Committee on Cancer tumor-node-metastasis (TNM) classification has been updated by the 7th edition in 2010. The objective of the study was to evaluate cancer-specific survival (CSS) in patients with renal cell carcinoma (RCC) and assess the concordance of 2002 and novel 2010 TNM primary tumor classifications. Materials and Methods: A retrospective analysis of RCC registries from 25 institutions of the Urooncology Association of Turkey Renal CancerStudy Group was performed. Patients with RCC had a radical or partial nephrectomy. The database consisted of 1889 patients. Results: Median follow-up time was 25 months (interquartile range: 11.2-47.8). The 5-year CSS rate for pT1a, pT1b, pT2a, pT2b, pT3a and pT4 tumors were 97% [95% confidence interval (CI): 0.93-0.99], 94% (95% CI: 0.91-0.97), 88% (95% CI: 0.81-0.93), 77% (95% CI: 0.64-0.86) 74% (95% CI: 0.65-0.81) and 66% (95% CI: 0.51-0.77), respectively according to the 2010 TNM classification (p<0.001). CSS comparisons between pT1a-pT1b (p=0.022), pT1b-pT2a (p=0.030), pT3a-pT3b (p<0.001) and pT3b-pT4 (p=0.020) were statistically significant. Conversely, pT2a-pT2b (p=0.070) and pT2b-pT3a (p=0.314) were not statistically significant. Multivariable analyses revealed the pT stage in the 2010 TNM classification as an independent prognostic factor for CSS (p for trend=0.002). C-indexes for 2002 and 2010 TNM classifications were 0.8683 and 0.8706, respectively. Conclusion: Subdividing pT2 does not have a CSS advantage. Moving adrenal involvement to pT4 yielded a more accurate prognosis prediction. T stage and LNI are independent prognostic factors for CSS in RCC. Overall, the novel 2010 TNM classification is slightly improved over the former one. However, shown by C-index values, this improvement is not sufficient to state that 2010 TNM outperforms the 2002 TNM.
Keywords: Renal cell carcinoma; kidney cancer; 2010 tumor-node-metastasis; primary tumor classification; ACCURACY; SIZE; RECLASSIFICATION; SYSTEM; GRADE